Sentiment Analysis of Sexual Violence on Twitter: Emotions, Public Perception, and Discourse - Jatiningsih, Oksiana; Siahaan, Sanggam Magda Lasmaria (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Sexual violence has captured the attention of many people these days. Not only because the numbers tend to increase during the Covid-19 pandemic but also because of the locus. The problem answered in this research is what Twitter users' sentiments are about sexual violence and what Fairclough's analysis of this is. The criteria for the data to be retrieved are tweets with filters: tweets with Indonesian, having the keyword